Local Wisdom for Bamboo Wicker Products through a Community-Based Approach in Thailand - Saiyut Phupuy; Saksit Rittilun; Voranuch Ninkhet (Journal of Educational Issues, 2024)
The objectives were to study the state of community involvement in applying local wisdom to learning management, and how to involve local wisdom, such as bamboo wicker products, to manage learning in educational settings. A select group of 85 in Kut Wa Subdistrict, Kuchinarai District, Kalasin Province, Thailand, research contributors consisted of those with bamboo wicker skills 10 persons, teachers 20 administrators, 10 school board members, 30 community leaders, and 15 arts and crafts conservation group representatives used qualitative research through group discussions and in-depth interviews. The tools used in the research are structured interviews and content-based data analytics. The results showed that community involvement in applying local wisdom and making bamboo wicker products helped people learn. The community asks for participation in providing information about local wisdom, by planning and implementing every step, coordinating every step, jointly evaluating it, seeking stakeholder benefits from local wisdom in their communities, and developing guidelines for applying local wisdom to bamboo wicker products in learning management. It discovered that all community organizations must help promote the management of local wisdom learning. The knowledge transferor must be a person who is skilled in making bamboo wicker in the community and who is considered a teacher of local wisdom. Teachers in the school must be the liaison between the community, and the school in bringing local wisdom matters into the school premises, which must be documented in a handbook for making bamboo wicker products, with which learners can apply the advice to their learning through hands-on learning.